2012
DOI: 10.17925/ohr.2012.08.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin’s Lymphoma in Adolescents and Young Adults

Abstract: Adolescents and young adults (AYAs) are defined as those individuals between the ages of 15 and 39 years.1 AYAs with cancer are considered a vulnerable group, in large part due to psychosocial challenges in this population, including lack of insurance, low rates of clinical trial enrollment, issues pertaining to independence, and concerns about body image and fertility. Hodgkin's lymphoma (HL) is the most common cancer observed among AYAs. 6 There is a slight overall male predominance in this age group, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Adolescents aged 15–18 treated in the United Kingdom between 1969 and 1998 years showed OS rates lower than those of young adults, aged 20–25 [ 36 , 37 ]. It is not very easy to make a comparison with these studies, because of the old therapeutic regimens applied, together with old staging systems such as laparotomy and splenectomy, which are no longer considered appropriated [ 38 ]. In the period 1978–2003, a Greek study showed a progressive improvement in the OS of the 16–23-year-old AYAs treated with three consecutive adult chemotherapeutic regimens [ 39 ] and the more recent studies performed between 1979–2013 in Europe and Canada registered 5-year OS rates even higher than 90% [ 23 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents aged 15–18 treated in the United Kingdom between 1969 and 1998 years showed OS rates lower than those of young adults, aged 20–25 [ 36 , 37 ]. It is not very easy to make a comparison with these studies, because of the old therapeutic regimens applied, together with old staging systems such as laparotomy and splenectomy, which are no longer considered appropriated [ 38 ]. In the period 1978–2003, a Greek study showed a progressive improvement in the OS of the 16–23-year-old AYAs treated with three consecutive adult chemotherapeutic regimens [ 39 ] and the more recent studies performed between 1979–2013 in Europe and Canada registered 5-year OS rates even higher than 90% [ 23 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%